Education, Communal Norms, and Environmental Health: A Study of Darul Muttaqien and Jam’iyyah Islamiyyah Islamic Boarding Schools in Addressing Tuberculosis - Raharyanti, Fenny; Sumantri, Arif; Jauharoh, Siti Nur Aisyah; Jalaludin, Juliana (JURNAL INDO-ISLAMIKA, 2024)
Tuberculosis (TB) cases in Indonesia are the second rank after India. This necessitates an investigation into behavior, communal norms, habits, and facilities present in educational institutions, particularly Islamic boarding schools.  The objectives of this study examined the above-mentioned aspects concerning the prevention of TB in Islamic boarding schools with or without Puskestren or Islamic boarding school health post contributions. This studywasconductedatDarulMuttaqienand Jam’iyyah Islamiyyah Islamic Boarding Schools. For quantitative: parameter scores are accumulated and compared significantly between the two Islamic boarding schools using an independent test (CI:95%,α:0.05), focusing on assessing the environments of the Islamic boarding schools, student questionnaires, and indoor air quality measurements, including humidity, lighting, temperature,inaccordancewithPermenkes1077/2011. Qualitative in-depth interviews are used through health ethnography (traditions and value assessments). The result is that activating Poskestren for Islamic boarding schools has a better impact on implementing clean and healthy living behavior and preventing disease, especially TB.